Determining the Quality of Educational Climate in a Private Medical College in Bangladesh via the ‘Dundee Ready Education Environment Measure’ Instrument - Mainul, Haque; Masuda, Mohsena; Smita, Debsarma (2016)
Background: The educational environment is an important determining factor of an effective curriculum. An enriched learning environment can lead to increased satisfaction, achievement and success as a practitioner. The educational environment has been defined as “environment experienced or perceived by the students as well as by the teachers”. Learning environment research seeks to assess the students’ perceptions of their environment and can guide medical teachers to introspect, devise, and incorporate the best learning strategy for the improvement of the educational environment. The recent concern to enhance quality assessment procedures in the health professions, and institutions have led to renewed interest in students’ perceptions of the educational environment. The aim of this study is to evaluate, by way of students’ perceptions, the overall education environment, as well as, other aspects of the educational environment of Ibrahim Medical College, Bangladesh. Methods: This crosssectional survey was conducted among the medical students in the year 2015, who were enrolled in the undergraduate MBBS program. DREEM questionnaire was used for data collection. The data was later regrouped according to the five domains. SPSS, IBM 20 has been used for data analysis. Results: Among the 416 student participants, 277 were female (67%), and 139 were male (33%). Comparison of the mean scores of pooled total and 4 sub-scales revealed no significant difference between genders, whereas in Students’ Academic Self-Perceptions scale average rating for a male was found statistically significantly higher (p<0.05). Conclusion: This study suggests that students, in general, hold positive perceptions of their course environment. These results can serve as a baseline for a longitudinal quality assessment of pupils’ perceptions of the college.